Avaliação na Educação de Jovens e Adultos em São Bernardo do Campo: um caminho a ser construído da exclusão à emancipação - Martins, Izaura Naomi Yoshioka (2021)
This research aims to build paths towards an emancipatory evaluation in the Young and Adult Education (YAE) course. The students in this kind of education have, in their life trajectories, in some way, the denial of the right to education. Many of these students, at the end of the school term, are evaluated with unsatisfactory learning and fail, and EJA, according to the CNE/CEB Opinion no. 11 of 2000 National Curricular Guidelines for Youth and Adult Education, should be the payment of an unrepaired social debt to people who did not have access, permanence, or success in school. Thus, the relevance of this project is based on the defense of the right to school success of EJA students, who will not be able, in a second passage through the school benches (or first), to suffer, again, another denial, having the evaluation as responsible. Based on this problem, the proposal to conduct a survey with some educators to reflect on an evaluation with emancipatory characteristics emerged. The research took place in São Bernardo do Campo (SP), as the curricular guidelines of the EJA in that municipality are based on the critical-liberating curriculum, based on a Freirean conception, a necessary condition for the realization of an emancipatory evaluation. To overcome evaluation as a form of oppression, exclusionary, unfair, which considers the subject as an object, a literature review was conducted on issues related to EJA, mainly involving curriculum and evaluation. This study supported the carrying out of participatory action research, with formative actions and dialogues with educators. In this sense, study meetings were held on the characteristics of EJA students, covering the way they learn and how they perceive themselves as subjects in this process. In this way, it was possible to understand the necessary conditions for carrying out an emancipatory evaluation. In addition, the analysis, both documental and content, pointed out the need, in several aspects, to overcome the contradiction of carrying out an education based on popular education in a formal education system